Assessing the Productivity, Quality and Profitability of Orange Fleshed Sweet Potatoes Grown in Riverbank of the Tista Floodplain Agro-Ecological Zone of Bangladesh - Mahmud, A.A.; Alam, M.J.; Heck, S.; Grüneberg, W.J.; Chanda, D.; Rahaman, E.H.M.S.; Molla, M.S.H.; Anwar, M.M.; Talukder, M.A.A.H.; Ali, M.A.; Amin, M.N.; Alhomrani, M.; et al. (MDPI, 2021)
Orange fleshed sweet potatoes (OFSP) are desirable for high productivity and profitability and their distribution to improve the nutrition of river bank inhabitants of Gaibandha and Rangpur districts of Bangladesh. In this context, a field trial was conducted in two riverbank-based farmers’ fields such as Saghata, Gaibandha, and Pirganj, Rangpur, particularly in the Active Tista Floodplain Agro-ecological Zone of Bangladesh. Four OFSP varieties were evaluated, i.e., G1: BARI SP-8; G2: BARI SP-12; G3: BARI SP-14; G4: BARI SP-15, along with one local cultivar as a control (Red skin with white flesh). Significant variations among the sweet potato genotypes were noted for a number of tuberous roots plant−1, length of root diameter of roots, tuberous root weight plant−1, root yield (fresh), root yield (dry), beta-carotene yield, as well as energy output. Over the locations, BARI SP-12 produced about 73% higher root yield (32.00 t ha−1) and it was like the BARI SP-8 (31.07 t ha−1), which produced about 68% higher yield in comparison with local cultivar (18.51 t ha−1). Across the location, BARI SP-8 performed better in root yield (31.89 t ha−1) in Gaibandha, 69% superior to local cultivar, whereas BARI SP-12 performed better in Rangpur (33.66 t ha−1), which was 86% greater than the local sweet potato cultivar. Considering the root dry yield production, BARI SP-8 produced the highest in the Gaibandha location after that Rangpur location. Further, BARI SP-14 had wider adaptability and stability over the year and location depended on the AMMI model. The beta carotene yield (Vitamin-A precursor) ranged 336–2957 kg ha−1 among the OFSP varieties, whereas the highest (2957 kg ha−1) carotene was recorded in BARI SP-14, similar to BARI SP-15 (2952 kg ha−1) but was much lower in BARI SP-8 and BARI SP-12. Moreover, BARI SP-8 and BARI SP-12 were also economically profitable in terms of gross margin (3233 and 3364 US$ ha−1, respectively), net return (3039 and 3170 US$ ha−1, respectively) and BCR (3.21 and 3.31, respectively, vs. 1.91) due to higher returns with a similar production cost of the local cultivar. The results suggested that BARI SP-8 is economically profitable in the riverbank areas of Gaibandha, and BARI SP-12 is suitable for the riverbank areas of Rangpur.